STRUCTURE OF TROOPS DURING THE RULE OF THE BABURIDS - Shamsiddinov Ulugbek Nurmurodovich (American Journals, 2025)
This article describes the composition, structure, types of troops, the positive aspects of officials during the rule of the Baburids in Middle Asia, of the Middle Ages.
Keywords: Baburids, army, king, bodyguard, military troops, gun, cavalry, bullet, Indian area, Akbarshakh, kingdom, security service.